Media and Participatory-Driven Communication Strategies in Raising Public Awareness of River Rehabilitation - Heni Nuraeni Zaenudin; Ahmad Fahrul Muchtar Affandi; Kokom Siti Komariah; Bagus Aditya Susanto; Alwan Husni Ramdani; Arrafi Malika Ardy (UPT Publikasi Ilmiah UNISBA, 2026)
River degradation poses a serious threat to ecological stability and global public health. While environmental awareness continues to grow, it is often not accompanied by commensurate concrete action. This study aims to identify factors that bridge the gap between awareness and action in river rehabilitation programs. Through a systematic literature review of 46 academic articles (2020–2025) grounded in the SMCR communication model, this study examines the mechanisms that translate awareness into collective action. Key findings reveal a